2019
DOI: 10.3390/s19194107
|View full text |Cite
|
Sign up to set email alerts
|

Detecting IoT Devices and How They Put Large Heterogeneous Networks at Security Risk

Abstract: The introduction of the Internet of Things (IoT), i.e., the interconnection of embedded devices over the Internet, has changed the world we live in from the way we measure, make calls, print information and even the way we get energy in our offices or homes. The convenience of IoT products, like closed circuit television (CCTV) cameras, internet protocol (IP) phones, and oscilloscopes, is overwhelming for end users. In parallel, however, security issues have emerged and it is essential for infrastructure provi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…The term 10 6 in Equation ( 4) just simplifies Equation (3) by converting time (or) latency (i.e., time for one PM) from microseconds to seconds. The time (or) latency mentioned in column 6 of Tables 4 and 5 is calculated by using Equation (5). time (or) latency = required clock cycles (CCs) operational clock f requency (in MHz)…”
Section: Performance Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…The term 10 6 in Equation ( 4) just simplifies Equation (3) by converting time (or) latency (i.e., time for one PM) from microseconds to seconds. The time (or) latency mentioned in column 6 of Tables 4 and 5 is calculated by using Equation (5). time (or) latency = required clock cycles (CCs) operational clock f requency (in MHz)…”
Section: Performance Metricmentioning
confidence: 99%
“…Due to this enormous communication of IoT devices through a cloud, they are subject to malicious attacks [4]. Security concerns arise, and therefore various threats and attacks may occur as data owners have no control over the data management [5]. Consequently, the importance of data security and the availability of limited resources provoke us to explore recent low-complexity cryptographic schemes [6].…”
Section: Introductionmentioning
confidence: 99%
“…The attacks met on this layer include physical cloning (counterfeiting) [ 9 , 21 , 22 ], malware, spyware [ 9 ] and physical attacks (intentional damage to the device, theft [ 9 ] especially for those deployed to work autonomously [ 23 ]). Agarwal et al [ 24 ] developed two tools to detect IoT devices in heterogeneous networks and to retrieve device-related data (manufacturer, model, firmware version) and they concluded that many IoT devices manufacturers do not secure the devices at all. When referring to IoT devices, one cannot implement the standard heavyweight, complex techniques [ 19 ] to secure the devices belonging to the layer.…”
Section: Security In the Internet Of Thingsmentioning
confidence: 99%
“…The use of scanners to find devices of a certain type is illustrated in [12] where researchers show how Shodan, Masscan and Nmap can be used to find specific IoT models that are vulnerable. Similarly, researchers analyzed the network of CERN, trying to identify IoT devices using web-scraping [1]. They identified all devices and profiled them, first by scanning their open ports, and then by scraping their web interface when they had one.…”
Section: Related Workmentioning
confidence: 99%